A critical discourse analysis on Jokowi and Prabowo’s tweets during 2019 presidential election - Dwi Santoso; Anggita Dyah Kusuma Wardani (Association for Scientific Computing Electrical and Engineering (ASCEE), 2021)
This paper aims to present critical discourse analysis on Jokowi and Prabowo's tweets during the 2019 presidential election. This paper will focus on critical discourse analysis, especially on the discourse structure of Jokowi and Prabowo's tweets and the communication strategies used by Jokowi and Prabowo during the presidential election. This research uses qualitative methods. The data obtained by the researcher comes from tweets written by Jokowi and Prabowo during the 2019 presidential election campaign. The data collection method used is the observation method by observing Jokowi and Prabowo's Twitter accounts. After collecting the data, the researcher classified the discourse structure using Van Dijk's discourse analysis concept in Jokowi and Prabowo's Tweets. The results of this study found elements of macrostructure (theme), superstructure (scheme), and microstructure consisting of semantic elements (background, detail, intention, presupposition), syntax (sentence form, coherence, conditional coherence, distinguish coherence, disavowal, pronoun), stylistic elements (lexicon) and rhetorical elements (graphology and metaphor) in tweets written by Jokowi and Prabowo. Furthermore, Jokowi and Prabowo used strategic communication campaign stage 3,